Semiconductor Superlattices: Growth and Electronic Properties - Grahn H T (World Scientific, 1995)
This book surveys semiconductor superlattices, in particulartheir growth and electronic properties in an applied electric fieldperpendicular to the layers. The main developments in this field,which were achieved in the last five to seven years, aresummarized. The electronic properties include transport throughminibands at low electric field strengths, the Wannier-Starklocalization and Bloch oscillations at intermediate electric fieldstrengths, resonant tunneling of electrons and holes between differentsubbands, and the formation of electric field domains for largecarrier densities at high electric field strengths.